Inquietações do existente: cinema como filosofia em Lars von Trier - Lima, Fransmar Barreira Costa (2018)
This essay intends a study of the Danish film-maker's work, Lars von Trier, as a grounding for the "cinema-thougt" that, when incorporated by a reader who assumes the reflexion in the existence, develops significant reviews. We call this reader "inspectador", because he is the initiative of incorporating the "restlessness" of the director and of assuming movie's situations in his subjectivity. The first part of the research analyzes the cinema as philosophy form Lars von Trier ideas, where the "inspectador"'s role is defined, the methodology of indirect communication and the cinema as possibility. This part also discuss the grounding and references that founds the problematic in Lar von Trier's work and how his movies stand out as "cinema-thougt. The second part analyzes the Cinema as philosophy from the "restnessless" of the existent, that is, visits Lars von Trier's production in order to reflect questions that arise in especific moments of his movie: as the Dogma 95 (Idioterne - #2, 1998), and the movies that precinds the correct formulation of the scenario, substituited by a "plan-map", as Dogviller (2003) e Manderlay (2005).